Pelaksanaan Fungsi Manajemen (Planning, Organizing, Actualling, Controlling) Pada Manajmeen Masjid Al-Akbar Surabaya - Faiz Alan Fahmi; A.Syifa’ul Qulub (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this research is to knowing the role of asset management in an attempt to managing financial independence and optimizing economic activities in Masjid Al-Akbar Surabaya. This research uses qualitative method with descriptive case study, while collecting the data uses purposive technique to specify the informan. The data used in this research isobtained by semi-structured interview, observation, and documentation. This research also uses triangulation techinique in checking the data validation. Triangulation is an examination technique which enables to use one or two another sources for validation or verification. The result of this research showing that asset management of Masjid Al-Akbar has been operated in accordance with asset management’s functions which is including planning, organizing, implementing, and controling which then result in financial indepedence of Masjid Al-Akbar Surabaya.